Variables asociadas al desempeño profesional del egresado de la Escuela de Formación Profesional de Educación Secundaria de la Especialidad de Lengua-Literatura de la Facultad de Ciencias de la Educación y Humanidades de la Universidad Nacional de la Amazonía Peruana Iquitos 1996-1998 - Vela Amasifuen, Patricia Elena (2000)
The present research aimed to determine the relationship between methodological strategies, educational infrastructure, and teacher qualities with the professional performance of graduates from the Professional School of Secondary Education, specializing in Language and Literature, at the Faculty of Education and Humanities of the National University of the Peruvian Amazon (UNAP) during the period 1996–1998. The study was non experimental with a correlational design, involving a population of 34 graduates. A structured questionnaire was administered to the principals of the educational institutions where the graduates were employed. The results showed that between 69% and 72% of the teachers demonstrated satisfactory professional performance, while the remaining participants exhibited lower levels. Likewise, 58.8% employed appropriate methodological strategies, and 61.8% worked in institutions with adequate infrastructure. Regarding teacher qualities, 35.3% were rated as good, 35.3% as fair, and 29.4% as poor. Statistical analysis (Chi-square) confirmed significant associations between professional performance and the three independent variables: methodological strategies (X² = 20.4), infrastructure (X² = 16.07), and teacher qualities (X² = 7.99), with a significance level of 0.05. It is concluded that the improvement of teachers’ professional performance depends on continuous methodological updating, strengthening of institutional conditions, and the comprehensive development of the educator.